Allergenicity at component level of sub‐pollen particles from different sources obtained by osmolar shock: A molecular approach to thunderstorm‐related asthma outbreaks. Issue 2 (26th January 2021) - Cecchi, Lorenzo; Scala, Enrico; Caronni, Sarah; Citterio, Sandra; Asero, Riccardo
Abstract: Background: The so‐called "thunderstorm asthma" (TA) is an uncommon but dramatic outbreak of asthma attacks occurring during a thunderstorm in the pollen and moulds season. Mechanisms which make the pollen able to enter the deeper airways and provoke severe asthma symptoms are still unclear. Objective: To test the hypothesis that sub‐pollen particles (SPPs) originated from the rupture by an osmotic shock of pollen associated with TA contain allergens. Methods: After hydration, SPPs released from pollen grains of grass, pellitory, olive, cypress, ragweed and birch were isolated and determined by microscopy. Allergens were determined by in vitro ELISA inhibition tests indirectly using the sera from 10 polyreactive patients. An inhibition <50% was considered as negative, 50%‐75% moderate and > 75% complete. Results: The inhibition experiments showed that the SPPs from birch and cypress were unable to inhibit serum IgE reactivity to Bet v 1 and Cup a 1, respectively. Ragweed SPPs inhibited ragweed pollen extract and Amb a 1 by 75.8 ± 0.11% and 81.2 ± 0.15%, respectively. Olive and pellitory SPPs retained almost the whole IgE‐binding capability in all cases tested. Grass SPPs inhibited 32 ± 0.06% of Lolium perenne Lol p 1 and 65% of Phleum pratense extracts, but results were highly variable for individual allergens (97.5%‐0.03% for Phl p 2, 45.3 ± 0.12% for Phl p 5, 24.7 ± 0.22% for Phl p 6, and 38.3 ± 0.2% for Phl p 1). Conclusions: Inhibition experiments confirm the hypothesis that SSPs obtained after the osmotic shock of pollen involved in TA, namely grass, pellitory and olive tree pollen, contain allergens and therefore they can induce severe asthma attacks during thunderstorms.